Komunikator ustny jako performer właściwie ułożony i właściwie licencjonowany w przestrzeni publicznej - Stanisław Puppel (Studia Rossica Posnaniensia)
The present essay expresses the view that a human communicating agent who performs orally in the public space must be properly communicatively aligned and properly licensed in order to achieve communicative success. Communicative alignment and communicative licensing are manifestations of the principle of communicative alignment and the principle of communicative licensing, respectively. The two principles are assumed to act synergistically in both successful and unsuccessful communicative practices.